The new material battery based on Mg/C-π - Siburian, Rikson; Paiman, Suriati; Hutagalung, Fajar; Ali, Ab Malik Marwan; Simatupang, Lisnawaty; Simanjuntak, Crystina (Wiley-VCH Verlag GmbH & Co. KGaA, 2021)
Herein, the effect of the size of Mg clusters on graphene nano sheets (GNS) and N-GNS (C-π) is investigated. The dependence of the electric conductivities of C-π on the electrolytes was also explored. This work aims to clarify the size effect of Mg clusters on Mg/C-π and to study the effect of addition of electrolytes to C-π materials on their electrical conductivities and chemical interaction between Mg on GNS and N-GNS, respectively. GNS and N-GNS are synthesized by modified Hummers and N-dopant method at room temperature, respectively. Characterization of each material is carried out using X-ray diffraction (XRD), scanning electron microscope–energy dispersive X-ray (SEM–EDX), and multimeter. The results show that the Mg cluster are well deposited on GNS and N-GNS and the addition of Mg metal and electrolyte materials can increase the electrical conductivities of Mg/GNS (69.9301 μS cm−1) and Mg/N-GNS (96.1538 μS cm−1), comparing to graphite (26.7 μS cm−1) and anode of commercial battery (26.0 μS cm−1). The addition of electrolyte can also increase the reduction power of Mg metal particles and the electron mobility of Mg/GNS and Mg/N-GNS materials. Interestingly, the electrolyte could reduce the size of Mg clusters and modulate the mobility of electrons. Data conclude that Mg/GNS and Mg/N-GNS can be produced into battery electrodes with better electrical conductivity.